Perbedaan Pengaruh Terapi Audio Gelombang Alpha dan Gelombang Theta terhadap Daya Konsentrasi Otak pada Pemuda GMIM Tabita Sarongsong 1 Airmadidi 2 - Kawengian, Jooh; Rumampuk, Jimmy; Lintong, Fransiska (Medical Scope Journal, 2020)
Abstract: This study was aimed to determine the differences in the effects of audio alpha and theta waves on brain concentration power among youths of GMIM Tabita Sarongsong I Airmadidi II. This was a quantitative study with a cross-sectional design. Samples were 30 youths obtained by using the systematic sampling technique. The brain concentration power was measured by the results of solving modified mathematical problems. Data were analyzed by using descriptive analysis, the normality test of Kolmogrov-Smirov, the homogeneity test was sought by the Levene test, followed by t-test to obtain the difference in the effects of audio alpha and theta waves on the brain concentration power. The results showed the average test result, as follows: of alpha wave exposure was 8.80 while of theta wave exposure was 8.53. The t-test analysis showed a p-valued of 0.000 <0.05, this meant that there was a significant difference between the effects of audio alpha and theta waves on the brain concentration power. In conclusion, alpha and theta wave therapy could influence the brain concentration power among youths of GMIM Tabita Sarongsong I Airmadidi II, however, theta wave was more effective than alpha wave.Keywords: audio wave therapy, brain concentration powerAbstrak: Penelitian ini bertujuan untuk mengetahui perbedaan pengaruh audio gelombang alpha dan gelombang theta terhadap daya konsentrasi otak pada Pemuda GMIM Tabita Sarongsong I Airmadidi II. Jenis penelitian ialah kuantitatif dengan desain potong lintang. Pengambilan sampel menggunakan teknik sampling sistematis dengan jumlah sampel 30 orang. Daya konsentrasi otak diukur dengan hasil pengerjaan masalah matematika yang dimodifikasi. Analisis data penelitian menggunakan analisis deskriptif, uji normalitas Kolmogrov-Smirnov, uji homogenitas Levene, dilanjutkan uji-t untuk mengetahui perbedaan pengaruh audio gelombang alpha dan gelombang theta. Hasil penelitian menunjukkan bahwa rerata hasil ujian dengan paparan gelombang alpha sebesar 8,80 sedangkan hasil ujian dengan paparan gelombang theta sebesar 8,53. Hasil analisis uji-t menunjukkan nilai p=0,000 <0,05. Simpulan penelitian ini ialah terapi audio gelombang alpha dan theta dapat memengaruhi daya konsentrasi otak pada Pemuda GMIM Tabita Sarongsong I Airmadidi II namun gelombang theta lebih berpengaruh daripada gelombang alpha.Kata kunci: terapi audio gelombang, daya konsentrasi otakÂ